Discharge against Medical Advice at Neonatal Intensive Care Unit in Gujarat, India - Bhanu Devpura; Pranav Bhadesia; Somashekhar Nimbalkar; Sandeep Desai; Ajay Phatak (International Journal of Pediatrics)
Objective. We explored reasons for discharged against medical advice (DAMA) of neonates from a neonatal intensive care unit (NICU) through in-depth interviews of the parents/guardians. Methods. Of 456 babies admitted to NICU during April 2014 to March 2015, 116 babies were DAMA. Parents of randomly selected 50 babies of these 116, residing within 50 kilometers, were approached for in-depth interviews at their homes. Audio recordings were done and manually transcribed, analyzed in detail to explore common threads leading to DAMA. Basic demographic information of the newborns was retrieved from hospital records. Results. The prevalence of DAMA was 25.4%. Of 50 parents approached, 41 in-depth interviews were completed. Nonaffordability (38.6%), no improvement (14.6%), poor prognosis (12%), and inappropriate behavior of the patient relation office personnel (10.6%) were major factors contributing to DAMA. Parents of 6.6% neonates wanted guarantee of survival and 5.3% parents reported poor behavior of nurses. No gender bias was observed related to DAMA. One-third of neonates (34.1%) were DAMA on first day of admission. Conclusions. The issue of DAMA needs attention. Besides nonaffordability and clinical characteristics of the baby, communication (breaking bad news, counseling, etc.) and lack of adequate infrastructure for relatives emerged as modifiable factors leading to DAMA.